Research trends of ferroptosis and pyroptosis in Parkinson’s disease: a bibliometric analysis - Wu, Zihua; Zhong, Kexin; Tang, Biao; Xie, Sijian (Frontiers in Molecular Neuroscience, 2024)
Objective: This study aims to visualize the trends and hotspots in the research of "ferroptosis in PD" and "pyroptosis in PD" through bibliometric analysis from the past to 2024.Literature was retrieved from the Web of Science Core Collection (WoSCC) from the past to February 16, 2024, and bibliometric analysis was conducted using Vosviewer and Citespace.Results: 283 and 542 papers were collected in the field of "ferroptosis in PD" and "pyroptosis in PD". The number of publications in both fields has increased yearly, especially in "ferroptosis in PD," which will become the focus of PD research. China, the USA and England had extensive exchanges and collaborations in both fields, and more than 60% of the top 10 institutions were from China. In the fields of "ferroptosis in PD" and "pyroptosis in PD", the University of Melbourne and Nanjing Medical University stood out in terms of publication numbers, citation frequency, and centrality, and the most influential journals were Cell and Nature, respectively. The keyword time zone map showed that molecular mechanisms and neurons were the research hotspots of "ferroptosis in PD" in 2023, while memory and receptor 2 were the research hotspots of "pyroptosis in PD" in 2023, which may predict the future research direction.This study provides insights into the development, collaborations, research themes, hotspots, and tendencies of "ferroptosis in PD" and "pyroptosis in PD". Overall situation of these fields is available for researchers to further explore the underlying mechanisms and potential treatments.